Expert Frames: Scientific and Policy Practices of Roma Classification. By Mihai Surdu. Budapest: Central European University Press, 2015, 267 pp., ISBN 978-963-386-113-4. - Yaron Matras (Social Inclusion, 2015)
The book offers a critique of current political and academic discourse on Roma, and calls for a “de-politicisation” of Romani ethnicity. While the critique of various disciplines’ approaches to Roma is pertinent, the book fails to acknowledge the solid linguistic evidence for the Indian origin of the Roma.